The Concept of People's Sovereignty Towards The Appointment of The Ideal Acting Regional Head - Hifdillah, Achmad Aldy; Negara, Tunggul Anshari Setia; Susmayanti, Riana (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This research aims to criticize the appointment of Acting Regional Heads as part of legal conflicts that are contrary to the constitution. The appointment of Acting Regional Heads who do not involve the people directly, causes a perception that people's sovereignty is sidelined for the sake of administrative efficiency. Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia is above the Election Law and the regulations under it, so that the interpretation of this regulation is not harmonious can trigger a polemic. This study uses doctrinal/normative research with a statute approach, conceptual approach, and case approach. The results of this study describe the concept of the appointment of Acting Regional Heads as an irrational part and has the potential to weaken the sovereignty of the people as enshrined in the staatfundamental norm (1945 Constitution) or grundnorm (Pancasila), the content element in the provisions for the appointment of Acting Regional Heads is full of non-democratic conditions so that these provisions need to be reviewed by prioritizing the aspect of people's participation. Therefore, it is necessary to strengthen the representation, participation of the people, and democratic mechanisms to maintain the sustainability of an inclusive and equitable political system.